Quantitation of six steroid hormones by ultra‐performance liquid chromatography–tandem mass spectrometry in plasma and prefrontal cortex samples from rats with chronic unpredictable mild stress‐induced depression. (4th July 2021) - Zhu, Ying; Han, Xuemei; Li, Xixuan; Qin, Yanjie; Rang, Ying; Zhai, Xuejia; Lu, Yongning
Abstract: Steroid hormones such as glucocorticoids and their metabolites are closely related to mental diseases and neuroendocrine diseases. Quantitative analysis of these substances will help in understanding their roles in related research fields. In this study, an ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) method was developed to detect the concentration of corticosterone (CORT) and its metabolites, progesterone (PROG) and testosterone in rat plasma and prefrontal cortex (PFC), and was applied to investigate the changes in hormones in rats with depression induced by chronic unpredictable mild stress (CUMS). The method was shown to be linear in the quantitation range for all analytes. Intra‐ and inter‐day accuracy and precision were between 80% and 120%. Furthermore, we found that the level of CORT in plasma and PFC increased, whereas that of 11‐dehydrocorticosterone (11‐DHCORT) as well as the ratio of 11‐DHCORT and CORT declined in rats with CUMS‐induced depression. The trends of these changes in central PFC and peripheral plasma were consistent. In conclusion, this study successfully established an UPLC–MS/MS method for simultaneous measurement of CORT and its metabolites, PROG and testosterone in rat plasma and PFC, and applied it to rats with depression. The method could be further applied to the research of depression and diseases related to these steroid hormones.